2022
DOI: 10.1186/s12935-022-02637-4
|View full text |Cite
|
Sign up to set email alerts
|

LINC00893 inhibits the progression of prostate cancer through miR-3173-5p/SOCS3/JAK2/STAT3 pathway

Abstract: Background Prostate cancer (PCa) is one of the most common malignant tumors in the male urinary system. In recent years, the morbidity and mortality of PCa have been increasing due to the limited effects of existing treatment strategies. Long non-coding RNA (lncRNA) LINC00893 was reported to inhibit the proliferation and metastasis of papillary thyroid cancer cells, but its role in PCa has not been reported. This study aims to investigate the role and underlying mechanism of LINC00893 in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…For instance, LINC00893 o overexpression suppresses the proliferation, migration, or invasion of gastric cancer cells and regulates epithelial-mesenchymal transition by binding with RBFOX2 ( 35 ). LINC00893 inhibits the progression of prostate cancer through the miR-3173–5p/ SOCS3 / JAK2 / STAT3 pathway ( 36 ). LINC00893 overexpression abrogates the proliferation and migration abilities of papillary thyroid cancer cells via the PTEN/AKT pathway ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LINC00893 o overexpression suppresses the proliferation, migration, or invasion of gastric cancer cells and regulates epithelial-mesenchymal transition by binding with RBFOX2 ( 35 ). LINC00893 inhibits the progression of prostate cancer through the miR-3173–5p/ SOCS3 / JAK2 / STAT3 pathway ( 36 ). LINC00893 overexpression abrogates the proliferation and migration abilities of papillary thyroid cancer cells via the PTEN/AKT pathway ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the expression of lncRNA LINC00265 was up-regulated in osteoarthritis patients and directly suppressed the expression of miR-101-3p; conversely, LINC00265 knockdown alleviated cell apoptosis and inflammation induced by caspase-3 in osteoarthritis [ 48 ]. Additionally, lncRNA LINC00893 regulated the suppressor of SOCS3/JAK2/STAT3 pathway by acting as a ceRNA to bind with miR-3173-5p in patient with prostate cancer [ 49 ]. The activation of JAK/STAT signaling pathways has diverse functions in the pathogenesis of sepsis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…numerous studies have indicated that the self-renewal and proliferation of SScs are regulated by various factors, including lncrnas (19,20). recent research has revealed that the expression of linc00893 is inversely correlated with cell proliferation in various types of cancer and that it serves a pivotal role in inhibiting tumor progression (21)(22)(23)(24). However, the relationship between linc00893 and SScs remains unclear.…”
Section: Discussionmentioning
confidence: 99%